Determinan Produktivitas Kerja Karyawan PT. Perkebunan Nusantara XIII - Ria Wanda Krisitanti; Subarjo Subarjo (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This study aims to analyze the influence of leadership style, work discipline and work motivation on work productivity. The sample in this study was 87 people who were employees of Perkebunan Nusantara XIII Kebun Ngabang. The data collection technique used was by distributing questionnaires. The results of the instrument test stated that the data in this study were valid and re-labeled. The classical assumption test stated that in this study it was normally distributed, free from multicollinearity and heteroscedasticity. The results of the study showed that: (1) Leadership style has a positive and significant effect on work productivity. (2) Work discipline has a positive and significant effect on work productivity. (3) Work motivation has a positive and significant effect on work productivity. These results have an impact on further researchers to assess work productivity in various companies and use other variables besides those in this study. The results of this study give the impression that PT Perkebunan Nusantara XIII Kebun Ngabang needs to optimize leadership style, work discipline and work motivation in order to create work productivity so that it can create good company performance.